Robotic-assisted hip and knee arthroplasty: a bibliometric analysis using the Scopus database - Kow, Ren Yi; Abdul Rani, Rizal; Mohamad Nazarallah, Mohamad Hilmi; F. Leong, Juzaily; Hayyun, Muhammad Fathi; Low, Chooi Leng; Zulkifly, Ahmad Hafiz; Mohamad Yahaya, Nor Hamdan (Springer Nature, 2024)
Robotic-assisted hip and knee arthroplasty represents cutting-edge advancements in orthopedic surgery, harnessing robotic technology to enhance precision, improve clinical outcomes, and facilitate intraoperative procedures. In these robotic-assisted surgeries, the robotic systems assist surgeons in planning and executing joint replacement surgeries, thereby facilitating personalized implant positioning and optimizing the fit and alignment of hip and knee implants. Despite the increasing attention garnered by robotic-assisted hip and knee arthroplasty in recent years, a comprehensive bibliometric analysis using the Scopus database has yet to be conducted. This bibliometric analysis reviews the Scopus database from 1961 until 2022 to investigate the literature on the field of robotic-assisted hip and knee arthroplasty. A total of 577 articles that satisfied the selection criteria were included in this review. The majority of the articles focus more on total knee replacement, compared to total hip replacement and unicompartmental knee arthroplasty. The overwhelming majority of the articles were authored by researchers and clinicians from the United States of America (USA) and the United Kingdom (UK). Similarly, most of the articles with the highest number of citations were authored by researchers and clinicians from these regions. This comprehensive bibliometric analysis using Scopus in the domain of robotic-assisted hip and knee replacement has the potential to act as a roadmap for researchers, clinicians, and policymakers, facilitating informed decision-making, promoting collaborative initiatives, and guiding the development of future studies to further advance the field of robotic-assisted hip and knee arthroplasty.